The EU approach to security provision in the Western Balkans and Horn of Africa - Rodt, Annemarie Peen; Tvilling, Johannes; Zaartsdahl, Peter Horne; Habbida, Nabila; Gillette, Erin; Simons, Savannah; Abdi, Khadir; Berglund, Jenny; Fernandez Arguedas, Virginia; Stojanovic Gajić, Sonja; Ignjatijević, Marija (Journal of Regional Security, 2019)
This article appraises the EU’s approach to preventing further insecurity in the Western Balkans and the Horn of Africa. The purpose of this endeavour is to determine whether EU efforts meet needs on the ground as well as in Brussels. The article identifies similar sources albeit different degrees of instability across the two regions. It reviews EU strategies and CSDP missions deployed in response and evaluates the effectiveness of two such missions: EULEX Kosovo and EUCAP Nestor/Somalia. The study does not find failures as such in the strategies developed or missions deployed, but it does conclude that while relatively effective from a EU perspective this approach is less effective in providing security on the ground.